PERINATAL RISK FACTORS FOR FETAL AND NEONATAL HYDROCEPHALUS - Мартыненко, Екатерина Игоревна; Жукова, Наталья Григорьевна; Ларькин, Игорь Иванович; Ларькин, Валерий Иванович; Кравченко, Елена Николаевна; Куклина, Лариса Владимировна (Mother and Baby in Kuzbass, 2023)
Hydrocephalus in children is the cause of severe brain damage and in some cases is the cause of disability.The aim of the research – to study perinatal risk factors for the formation of hydrocephalus in the fetus and newborns.Materials and methods. The anamnesis and the course of pregnancy were studied in 128 women (the main group) whose newborns were born with hydrocephalus or hydrocephalus developed early after birth, later these infants were operated on for this disease. All women had a high perinatal risk and were hospitalized for childbirth and delivered in the City Clinical Perinatal Center of Omsk in 2017-2022, their newborns were transferred to the second stage of nursing, and later they underwent surgical treatment. A retrospective study was conducted according to the «case – control» type. The comparison group included 128 pregnant women and their newborns, whose children did not have hydrocephalus.The results of the study showed that women whose children had hydrocephalus were more likely to have pregnancy complications such as preeclampsia (14.8 %), polyhydramnios (5.5 %), threatening miscarriage (46.1 %) and threatening premature birth (35.2 %), pregnancy more often ended with the birth of a fetus with extremely low body weight (10.2 %). Fetal growth retardation was detected in women of the main group 7 times more often (11.7 %) than in the comparison group (1.6 %; p = 0.002). Intrauterine infection was diagnosed in 38.3 % of patients in the main group and 9.3 % in the comparison group (p < 0.001), that is, 4 times more often. Placental insufficiency was detected in 32.8 % of pregnant women of the main group and 9.3 % of the comparison group (p < 0.001), that is, 3.5 times more often.Conclusion. A significant part of obstetric complications is a manifestation of intrauterine infection. The result of the progression of infection was the development of hydrocephalus. Congenital hydrocephalus is often accompanied by prematurity, asphyxia at birth, intraventricular hemorrhages and convulsions in a newborn.
Keywords: hydrocephalus; viral infections; intrauterine infection; perinatal risk factors; antenatal anomalies